(untitled) (Marketing Journal, 2025)
This article analyzes the factors affecting the mortgage market of Uzbekistan. It also highlights the economic essence and necessity of the “Escrow” system in the mortgage market. The article studies the experience of foreign countries and formulates scien tific proposals and theoretical conclusions for its implementation in the mortgage market of Uzbekistan. The article also offers practical analysis and theoretical solutions to the issues of improving mortgage financing in Uzbekistan.